Where have all the prophets gone? Perspectives on political preaching - Cilliers, Johan (Stellenbosch Theological Journal, 2016)
This article takes a brief look at the notions of voice, event, and experience within the communal paradigm of South African societies. This is followed by a description of different ways in which political and eschatological preaching has been understood within recent times, starting with the reverted eschatology of apartheid sermons, linked to the experience of fear; then the hopeful eschatology of Desmond Tutu’s sermons, evoking experiences of anticipation; and concluding with what could be called the present day vacuum in this regard: preaching that strives to maintain by means of introverted eschatology, contributing to experiences of uncertainty.